Analisis Kinerja Dome Solar Dryer Untuk Pengeringan Kopi Di Desa Karang Sidemen Kabupaten Lombok Tengah - Ridho, Rosyid; Khalil, Fakhrul Irfan; Saputra, Oki; Widhiantari, Ida Ayu; Puspitasari, Isnaini; Zulfikar, Wahyudi; Antesty, Sella; Afriana, Tina; Anugerah, M. Titan; Yusuf, Ahmad Rahman (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
Coffee drying is a crucial stage that influences the final product's quality and flavor. This process must be performed correctly to maintain the quality of the coffee beans and prevent mold growth. This study aims to compare two coffee drying methods, using a Solar Dome Dryer and direct sun drying. The research was conducted in Karang Sidemen Village, Central Lombok, using 100 kg of coffee beans, divided into two groups of 50 kg each for the two drying methods. The results showed that both methods successfully reduced the moisture content to 0%, but the drying with the Solar Dome Dryer was faster (4,320 minutes) compared to direct sun drying (4,380 minutes). The Solar Dome Dryer maintained a more stable temperature (50-60Â°C) and produced a more consistent drying rate, making it more efficient in preserving the quality of the coffee beans and preventing microbial contamination. This study recommends the use of Solar Dome Dryer for coffee drying in areas with high humidity and variable weather conditions.